PRINSIP DAN VARIASI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) PADA TINGKAT SEKOLAH MENENGAH PERTAMA ( SMP ) - Rosmaimuna Rosmaimuna (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Along with technological advances that are very influential on the development of education in schools, then the use of media (physical tools) learning must also adjust to the progress of these technologies. The use of media makes learning more effective and efficient. In addition, the development of education in Indonesia is increasingly changing and encouraging change efforts.Currently, learning in schools began to be adapted to the development of information technology. It causes changes and paradigm shifts in education. Learning that originally used only conventional or verbal lecture methods merely became a more active and enjoyable learning. Learning initially assumes students as passive objects accepting what they are from teachers, becoming learning that requires students to be active in the learning process. Active and fun learning requires a means that can be used as an intermediary in the learning process to enhance effectiveness and efficiency in achieving learning objectives, at least effective and efficient means in its form, its environmental components, its physical tools, and its communications.Similarly, Islamic Religious Education, especially the material (subject) Aqidah for High School Level Advanced First or more familiar with the title of junior high school. Psychological age students are psychologically early teenagers who start trying to recognize the identity and the opposite sex. So the planting of aqidah at this age should not be wasted. The role of teachers of Islamic Religious Education is expected to be active to make aqidah material is interesting and memorable to be studied and practiced in everyday life. For that dubutuhka variation of instructional media on the subject aqidah which can be material and reference for teachers to deliver aqidah material at the junior level. Of course the teachers must also understand and pay attention to the principles of the use of learning media first. Keywords: Principles, Variations, Learning Media